3 Steps Writing Strategy: Imitating-Reworking-Developing to Attract Interest in Writing Descriptive Writing in Improving Students Writing Ability - Rakhmanina, Lisa (Linguists : Journal of Linguistics and Language Teaching, 2019)
This study aims to find out whether 3-step-writing strategy could have a significant impact on the students 'writing results in descriptive writing and also to find out whether there is an impact of the interaction between 3-step-writing strategy on students' writing interest. The population in this study were Law Faculty students in the 2017-2018 academic year with a total of 25 students. In this study, sampling using purposive techniques that took two classes as samples and divided into two groups, namely: Experimental Group and Control Group. The Experimental Group learned to Write Descriptive by using 3-step-writing strategy. Data was collected by conducting tests (pre and post-tests) and questionnaires. The data obtained were analyzed using the T Test and Two-Way Anova Test with the help of the SPSS 22 Program. It showed significant different on students` English Writing achievement from pre-test to post-test and also from experimental and control group. Students also showed great interest on English Writing of Descriptive text by applying 3-step-writing strategy. It means that 3-step-writing strategy could improve students` English writing skill and could also  empower students to learn more.